The Gamaye pluton: a tectonic marker of the early Eburnean (Birimian) orogeny in the Kédougou-Kéniéba Inlier (West African Craton) - (:unkn) unknown (My University, 2024)
The Gamaye pluton belongs to the Paleoproterozoic Kédougou-Kéniéba Inlier (KKI), in the West AfricanCraton. It crops out as a N-S elongated body, with dimensions of ~24 x 9 km, east of a major crustaldiscontinuity, the sinistral, transcurrent Senegal-Mali Shear Zone (SMSZ). Also, as for other granitoids inthe KKI, it displays spatio-temporal relationships with world-class gold mineralizations (Lawrence et al.,2013). The pluton is made of a dominant, fine- to medium-grained and locally porphyritic leucocraticbiotite granite, associated with a subordinate, fine- to very-fine grained mesocratic granite. Apatite U-Pbgeochronology yields, for the main leucocratic facies, a date with relatively large uncertainties (2160.0 ±34.8), interpreted as the emplacement age of the pluton. An older apatite U-Pb age of 2294.6 ± 68.3 Ma,obtained for the mesocratic facies, is likely related to an inherited, early Paleoproterozoic component, asfound in other granitoids of the KKI through zircon U-Pb geochronology (e.g. Lambert-Smith et al., 2016).The mesocratic and leucocratic facies are both mylonitized close to the western margin of the pluton, in aroughly N-S-trending, sinistral transcurrent strike-slip shear zone, possibly a satellite of the SMSZ.Outside this high-strain zone, microstructures show that the Gamaye pluton has also undergone solid-state deformation and dynamic recrystallization of variable, but weak intensity. Measurements of theanisotropy of magnetic susceptibility, conducted on 54 samples, reveal paramagnetic signatures withbulk susceptibilities lower than 0.5×10-3 SI and a variation of the magnetic fabric shape, from oblate toprolate, towards the western mylonitic zone. The magnetic lineations are gently-plunging and orientedquite regularly, with a weighted mean orientation of N195°E/3°S. The magnetic foliations (weighted meanorientation of N24°E/23°E) are organized around a zone axis parallel to the average magnetic lineation, afeature commo
Keywords: African Research